Global, regional, and national burdens of Urolithiasis in adolescents and young adults aged 10–24 years from 1990 to 2021: a trend analysis based on the Global Burden of Disease Study 2021 - Wang, XinXin; Wei, XiuWang; Liang, JianBo; Xu, YangYang; Yang, DaMing; Wang, XiuJia; Huang, HuanWen; Chen, ChangSheng; Li, KaiQiang (Frontiers in Urology, 2025)
BackgroundUrolithiasis poses a significant health risk to adolescents worldwide, yet information on its burden and trends is limited. This study analyzed the evolving patterns of urolithiasis among 10-24-year-olds globally, regionally, and nationally from 1990 to 2021.MethodsThis study predicted the global burden of diseases and investigated urolithiasis incidence and disability-adjusted life-years (DALYs) in 10-24-year-olds. We reported cases, rates per 100,000, and AAPCs globally, regionally, and nationally. We explored trends across age groups, sexes, and SDI categories, using Joinpoint regression to identify the year with the most significant global trend shift.ResultsThe global incidence of urolithiasis among adolescents and young adults aged 10 – 24 years has increased modestly, from 321.5 per 100,000 in 1990 to 342.6 per 100,000 in 2021, with an average annual percent change (AAPC) of 0.2. A significant upward shift was observed in 2009. Regionally, Tropical Latin America saw the largest increase, with a rise from 155.1 per 100,000 in 1990 to 296.4 per 100,000 in 2021, and an AAPC of 2.07. In contrast, East Asia experienced the most significant decline, dropping from 214.2 per 100,000 in 1990 to 140.2 per 100,000 in 2021, with an AAPC of -1.37. Nationally, Brazil showed the highest increase, with an AAPC of 2.14, while the Russian Federation had the highest incidence in 2021, at 812.7 per 100,000. The middle-SDI quintile countries saw the largest increase in incidence, with an AAPC of 0.45. However, countries with high to middle and high SDI scores demonstrated a decrease in incidence. From 1990 to 2021, the incidence of urolithiasis increased more rapidly among females than males, with an AAPC of 0.26 and 0.16 respectively. By 2021, there were 6,467,487 cases globally, 57.8% of which were in males. The most significant increase in incidence was observed among those aged 20 – 24 years, with an AAPC of 0.29.ConclusionsThe global burden of urolithiasis in adolescents and youth is a significant health issue requiring international collaboration for better management. Enhancing diagnostic tools and implementing effective prevention and treatment methods are crucial.